Effects of Mindfulness-Based Stress Reduction on Depression in Adolescents and Young Adults: A Systematic Review and Meta-Analysis - Chi, Xinli; Bo, Ai; Liu, Tingting; Zhang, Peichao; Chi, Iris (Frontiers in Psychology, 2018)
Background: Mindfulness as a positive mental health intervention approach has been increasingly applied to address depression in young people. This systematic review and meta-analysis evaluated the effects of mindfulness-based stress reduction (MBSR) in the treatment of depression among adolescents and young adults. Methods: Electronic databases and references in articles were searched. Randomized controlled trials (RCTs) evaluating MBSR and reporting outcomes for depressive symptoms among young people aged 12 to 25 years were included. Data extraction and risk of bias assessment was conducted by two reviewers independently. Hedges’ g with a 95% confidence interval was calculated to represent intervention effect. Results: Eighteen RCTs featuring 2,045 participants were included in the meta-analysis. Relative to the control groups (e.g., no treatment, treatment as usual, or active control), MBSR had moderate effects in reducing depressive symptoms at the end of intervention (Hedges’ g = -.45). No statistically significant effects were found in follow-up (Hedges’ g = -.24) due to a lack of statistical power. Meta-regression found that the average treatment effect may be moderated by control condition, treatment duration, and participants’ baseline depression. Conclusion: MBSR had moderate effects in reducing depression in young people at posttest. Future research is needed to assess the follow-up effects of MBSR on depressive symptoms among adolescents and young adults.